Temperature phased anaerobic digestion of municipal sewage sludge: a Bardenpho treatment plant study - AKGÜL, DENİZ (My University, 2016)
The disposal of waste sludge generated from wastewater treatment plants (WWTPs) is a growing problem worldwide, and contributes to over 50% of the operating costs of current WWTPs. In this study, temperature-phased anaerobic digestion (TPAD) and conventional (single-stage) mesophilic anaerobic digestion were investigated in order to determine the most beneficial process for the intended digester facility to be constructed for the fermented primary and secondary sludge from a Bardenpho type biological nutrient removal plant. This was accomplished by considering several operational control parameters for three different sludge retention times. This study has shown that the TPAD system had significant improvement in biogas and methane production; solids and organic removal; pathogen reduction and dewaterability over the conventional digestion. In terms of overall volatile sulphur compounds formation normalized per volatile solids added, no significant effects were observed between TPAD and control digester.
Temperature phased anaerobic digestion of municipal sewage sludge